Potential virulence factors of Proteus bacilli. - Rózalski, A (1997)
The object of this review is the genus Proteus, which contains bacteria considered now to belong to the opportunistic pathogens. Widely distributed in nature (in soil, water, and sewage), Proteus species play a significant ecological role. When present in the niches of higher macroorganisms, these species are able to evoke pathological events in different regions of the human body. The invaders (Proteus mirabilis, P. vulgaris, and P. penneri) have numerous factors including fimbriae, flagella, outer membrane proteins, lipopolysaccharide, capsule antigen, urease, immunoglobulin A proteases, hemolysins, amino acid deaminases, and, finally, the most characteristic attribute of Proteus, swarming growth, enabling them to colonize and survive in higher organisms. All these features and factors are described and commented on in detail. The questions important for future investigation of these facultatively pathogenic microorganisms are also discussed.